(untitled) (Mongolian Journal of Arts and Culture, 2024)
This study explores the application of Artificial Intelligence (AI) concepts in the context of Hindu epics, particularly The Mahabharata. The research seeks to draw parallels between ethical dilemmas faced by characters in the scripture and the contemporary challenges of AI governance. The objective is to examine how the concepts of autonomy, responsibility, and moral decision-making, as depicted in these ancient scriptures, can inform modern discussions on the ethical use of AI. The study adopts a qualitative methodology, analyzing specific episodes from The Mahabharat in light of AI governance frameworks. Key episodes, such as Yudhisthira’s dice game, Krishna’s counsel to Arjuna, and the use of Krishna’s Sudarshana Chakra, are examined for their relevance to AI ethics, particularly the dangers of unchecked autonomy, the balance between autonomy and responsibility, and the ethical use of autonomous systems. The findings reveal that The Mahabharat provide rich analogies for contemporary AI governance issues. The texts emphasize the importance of ethical oversight, human control, and moral responsibility in decision-making processes, mirroring current debates around AI’s role in society. The principle of dharma is highlighted as a potential framework for governing AI systems, ensuring that they operate ethically and prioritize human welfare. In conclusion, the study suggests that insights from Hindu philosophy, particularly the concept of dharma, offer valuable ethical guidance for the development and regulation of AI systems, ensuring that these technologies serve humanity responsibly.